Y el luto sigue (and the grief continues): Latinx Immigrant's Experiences of Ambiguous Loss in the Age of Restrictive Immigration Policy. Issue 4 (22nd June 2021) - Sanchez, Elizabeth; Philbin, Sandy P.; Ayón, Cecilia
Abstract : Objective: Informed by Boss's ambiguous loss theory and an ecological perspective, this study examined Latinx immigrant mothers' experiences of loss associated with their immigration status and the restrictive immigration policy climate. Background: Undocumented participants strive to maintain international familial ties and experience loss in their inability to see or share a space with loved ones in their country of origin due to restrictive immigration policy and enforcement that inhibits their international mobility. Methods: In‐depth semistructured interviews were completed with 25 Latinx immigrant mothers who were mostly undocumented or members of mixed‐status families. Results: Findings support a model of transnational loss. Loss is experienced at premigration, upon arrival, and long after settlement. Participants' quotes illustrate their experiences of ambiguous, anticipatory, and complicated loss. In addition, transnational loss was described as a shared experience, one that impacted many undocumented immigrants in the United States and participants' family members. A subtheme, intergenerational loss, emerged in which children vicariously experienced their parents' loss. Conclusion: Transnational loss is disenfranchised because it is not socially recognized, leaving immigrants to mourn in silence. Implications: Practitioners serving immigrant communities should integrate grief and loss support through psychoeducation, assessments, and therapy. At a policy level, immigrants need to have the opportunity to adjust their status so that they can reclaim these lost social interactions.